2019
DOI: 10.7150/thno.36375
|View full text |Cite
|
Sign up to set email alerts
|

Fibrogenic fibroblast-selective near-infrared phototherapy to control scarring

Abstract: Rationale: Fibroblasts, the predominant cell type responsible for tissue fibrosis, are heterogeneous, and the targeting of unique fibrogenic population of fibroblasts is highly expected. Very recently, elevated glycolysis is demonstrated to play a pivotal role in the determination of fibrogenic phenotype of fibroblasts. However, it is lack of specific strategies for targeting and elimination of such fibrogenic populations. In this study, a novel strategy to use the a near-infrared (NIR) dye IR-780 for the targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…Moreover, persistent myofibroblast activation distinguishes pathological fibrosis from physiological wound healing, suggesting that therapies selectively inducing myofibroblast apoptosis could prevent progression and potentially improve established lung fibrosis. Consistent with our previous research that IR-780 can characterize HIF-1/glycolysis hyperactive cell population [ 68 , 69 ], we also identify that glycolysis enhances cell retention of IR-780 and may lead to severe inhibition of SDHA and excessive ROS in myofibroblasts, this offers the opportunity to successfully improve pulmonary fibrosis with IR-780 by targeting myofibroblasts apoptosis. To our knowledge, this is the first study to realize the prevention and treatment of lung fibrosis by suppressing SDH or SDHA with varying degrees in fibroblasts and myofibroblasts, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, persistent myofibroblast activation distinguishes pathological fibrosis from physiological wound healing, suggesting that therapies selectively inducing myofibroblast apoptosis could prevent progression and potentially improve established lung fibrosis. Consistent with our previous research that IR-780 can characterize HIF-1/glycolysis hyperactive cell population [ 68 , 69 ], we also identify that glycolysis enhances cell retention of IR-780 and may lead to severe inhibition of SDHA and excessive ROS in myofibroblasts, this offers the opportunity to successfully improve pulmonary fibrosis with IR-780 by targeting myofibroblasts apoptosis. To our knowledge, this is the first study to realize the prevention and treatment of lung fibrosis by suppressing SDH or SDHA with varying degrees in fibroblasts and myofibroblasts, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…7 C, glycolysis inhibitors significantly decreased the cellular uptake of IR-780, while fenofibrate did not, suggesting glycolysis enhanced cell retention of IR-780. We have reported that OATPs (organic-anion-transporting polypeptide), also known as solute carrier organic anion (SLCO), are the carriers of IR-780 [ 45 , 46 ], but the main OATP which induce IR-780 uptake varies in different tissues or cell types. Notably, the accumulation of IR-780 in myofibroblasts was significantly decreased when administered the OATPs inhibitor BSP (bromosulfophthalein) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The isolation of neonatal mouse fibroblasts was described previously. 17 Previous isolated primary human skin fibroblasts were used, and the protocol was approved by the ethics committee of the AMU. Cells were cultured in DuIbecco’s modified eagIe’s medium (DMEM) with 10% fetal bovine serum (Gibco), 100 U/mL penicillin, and 0.1 mg/mL streptomycin (Beyotime).…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al found that the hyperactive glycolytic fibroblast population is the main factor for ECM deposition during skin trauma, suggesting that glycolytic diversity is closely related to the heterogeneity of fibroblasts. Hyperactive glycolysis may be a functional phenotype in patients with fibrosis [ 10 ]. The enhancement of cellular glycolysis is usually caused by insufficient oxygen supply to the tissues, but the oxygen supply depends on the blood supply of the tissues.…”
Section: Adscs and Adsc-exos Indirectly Regulate Fibroblasts And Myof...mentioning
confidence: 99%
“…Fibroblasts play an important role in wound healing and scar formation [ 8 ], which are essential for ECM production, but overproduction may be detrimental to the outcome of scarring [ 9 ]. Myofibroblasts are considered to be the main fibrogenic cells in wound healing [ 10 ]. The regulation of some signaling pathways in fibroblasts and myofibroblasts is beneficial to reduce scar formation.…”
Section: Introductionmentioning
confidence: 99%